Seroprevalence of enterically transmitted hepatitis in North West India / Rekha Bachhiwal … [et al.] - Rekha Bachhiwal (Faculty of Medicine, 2016)
Introduction: To ascertain the seroprevalence of enterically transmitted Hepatitis A (HAV) and Hepatitis E (HEV) in cases with acute/subacute hepatitis attending a tertiary care hospital in North West India. Methods: A total of 2936 cases were examined for the presence of current infection with HAV and HEV, determined by demonstration of HAV-IgM and HEV-IgM antibodies using ELISA. Results: Overall seroprevalence for enterically transmitted hepatitis was found to be 24.89%. HAV IgM was present in 7.35% and HEV IgM was present in 17.54% of total cases. HAV infection was predominantly found in pediatric age group while HEV infection was mostly seen among adults. Male preponderance was noted. Enteric hepatitis cases occurred throughout the year. No definitive seasonal pattern was observed. Conclusion: Our data demonstrated high seropositivity of enterically transmitted hepatitis indicating the need for improvement in personal and public hygiene, and development of HEV vaccine.